Information and Communication Education (ICE): Guidance on the Dangers of Cyberbullying and Wise in Social Media for Teenagers at SMK Ma'arif 2 Sumedang - Arisara, Gita; Rahayu, Anita Sri; Dela Oktarifa Hidayat; Melisa Virginia N; Nurjanah , Nur; Radika Amelia; Siti Hamidah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
In this modern and advanced era, social media has become a tool and means of communication among teenagers so that they can connect with their friends. Social media can have both positive and negative impacts, one of which is cyberbullying. Cyberbullying occurs when a child is mocked, insulted, intimidated, or humiliated by another child through the internet. Therefore, we are conducting a community service activity (CSA) with the title Information And Communication Education (Ice): Guidance On The Dangers of Cyberbullying and Wise in Social Media For Teenagers at SMK Ma’arif 2 Sumedang. The goal is to increase students' knowledge about the concept of cyberbullying and its impacts. This activity was conducted in one of the classes at SMK Ma'arif 2 Sumedang on October 29, 2024, using lecture and discussion methods, targeting 53 12th-grade female students. The results show an increase in students' knowledge, attitudes, and behaviors regarding the dangers of cyberbullying. The recommendation for this activity is to provide direct education to students about the dangers of cyberbullying and how to wisely use social media.